Lentera Disabilitas and the Light of Inclusion: Serving Citizens and Advancing the Public Interest in Banjarbaru Land Office - Riszky Adhini Rachmi; Bintoro Wardiyanto; Erna Setijaningrum (Publikasi Indonesia, 2025)
This study analyzes the implementation of the Lentera Disabilitas program at the Banjarbaru Land Office as an example of inclusive public service focused on serving citizens and advancing the public interest. The program aims to enhance accessibility for persons with disabilities by providing disability-friendly facilities such as ramps, inclusive waiting rooms, special service counters, and multilingual service materials. It also emphasizes a cultural shift toward empathetic and respectful service behavior. This research uses a descriptive qualitative approach through in-depth interviews with an internal staff member (whose identity is anonymized upon request), direct observation, and document analysis. The findings show that the program enhances employee participation, fosters humanistic service values, and strengthens public trust, particularly among persons with disabilities. However, challenges remain, including the need for more trained staff and strengthened infrastructure. The program offers important lessons on the role of empathy, collaboration, and responsiveness in building inclusive public services.